Intra-Aortic Balloon Pumping in Acute Decompensated Heart Failure With Hypoperfusion: From Pathophysiology to Clinical Practice. (28th October 2021) - Baldetti, Luca; Pagnesi, Matteo; Gramegna, Mario; Belletti, Alessandro; Beneduce, Alessandro; Pazzanese, Vittorio; Calvo, Francesco; Sacchi, Stefania; Van Mieghem, Nicolas M.; den Uil, Corstiaan A.; Metra, Marco; Cappelletti, Alberto Maria
Abstract : Supplemental Digital Content is available in the text. Abstract : Trials on intra-aortic balloon pump (IABP) use in cardiogenic shock related to acute myocardial infarction have shown disappointing results. The role of IABP in cardiogenic shock treatment remains unclear, and new (potentially more potent) mechanical circulatory supports with arguably larger device profile are emerging. A reappraisal of the physiological premises of intra-aortic counterpulsation may underpin the rationale to maintain IABP as a valuable therapeutic option for patients with acute decompensated heart failure and tissue hypoperfusion. Several pathophysiological features differ between myocardial infarction- and acute decompensated heart failure–related hypoperfusion, encompassing cardiogenic shock severity, filling status, systemic vascular resistances rise, and adaptation to chronic (if preexisting) left ventricular dysfunction. IABP combines a more substantial effect on left ventricular afterload with a modest increase in cardiac output and would therefore be most suitable in clinical scenarios characterized by a disproportionate increase in afterload without profound hemodynamic compromise. The acute decompensated heart failure syndrome is characterized by exquisite afterload-sensitivity of cardiac output and may be an ideal setting for counterpulsation. Several hemodynamic variables have been shown to predict response to IABP within this scenario, potentially guiding appropriate patient selection. Finally, acute decompensated heart failure with hypoperfusion may frequently represent an end stage in the heart failure history: IABP may provide sufficient hemodynamic support and prompt end-organ function recovery in view of more definitive heart replacement therapies while preserving ambulation when used with a transaxillary approach.